PENGARUH MODEL PEMBELAJARAN INQUIRI TERHADAP HASIL BELAJAR SISWA PADA MATERI JAMUR DI KELAS X SMK NEGERI 1 RAMBAH TAHUN PEMBELAJARAN 2014/2015 - -, Heriyanto; Lestari, Rena; Lubis, Riki Riharji (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aim of this study was to determine learning outcomes of MP SMK N 1 Rambah students Class X by using inquiry learning model with quasi-experiment. Samples were the students in Class X. Result showed that studying biology in mushroomâs topic by using inquiry model learning was not effect significantly. But from the posttest, the experiment class was higher than control class with value 80,86 and the control class was 78,59. It can be concluded that there is no effect from inquiry model learning toward result of learning students in mushroomâs topic in Class X SMK N 1 Rambah in academic year of 2014/2015.